Islamic movement and human rights: Pertubuhan Jamaah Islah Malaysia’s involvement in the “Abolish Internal Security Act Movement,” 2000-2012 - Malik, Maszlee (IIUM Press, 2014)
Human rights has been acknowledged as one of the essential characteristics of good governance. Abuse of human rights is strongly associated with bad governance, which is believed by many to be a serious impediment to development and sustainable growth. Despite the active participations of Islamic movements in many parts of the political world, very little is known of their involvement in advocating human rights issues as part of their struggle for power. Nevertheless, as an Islamic movement and an Islamic revivalism actor in Malaysia, Pertubuhan Jamaah Islah Malaysia (JIM) has shown otherwise. JIM has resembled a different attitude towards the issue of human rights that they believe as an integrated and pertinent composition of good governance. By scrutinising their political activities and discourse since 2000, it becomes clear that JIM has been actively engaged in good governance and human rights issues, especially those that relate to the political rights of citizens through its involvement in the Abolish Internal Security Act (ISA) Movement (Gerakan Mansuhkan ISA). This paper examines JIM’s involvement in human rights issues with a special focus on its active and leading role in calling for the abolishment of the Internal Security Act (ISA).